(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
The article examines safety skills of future teachers of physical culture. Among principal safety skills of teachers of physical culture the following have been determined: ability to faultlessly execute objectives set, ability to forecast potential dangers. Methodology and grading scale for these skills evaluation has been presented in the article. Improvement of the defined safety skills has been shown via realization of pedagogical condition of “Orientation of pedagogical practice on realization of complex educational, health-improvement, and age-related objectives”. The formation and improvement of safety skills is one of the main conditions for the high-quality implementation of the professional activity of future physical education teachers. Among the important safety skills we have highlighted: the ability to carry out tasks without error and the ability to predict potential dangers. In the course of the conducted pedagogical experiment, the effectiveness of the specified pedagogical condition was confirmed: "Direction of pedagogical practice to solve complex educational, health and educational tasks." Implementation of this pedagogical condition was carried out through: careful planning of physical education lessons, analysis of professional actions, identification and efforts to reduce errors, efforts to form the future teacher’s sense of the reaction of the student’s body to physical exertion; formation of the future teacher’s sense of the time duration of the exercise, the use of a personal example of physical exercise, insurance, constant movement of trainee students together with students. The conducted pedagogical experiment proved effectiveness of the suggested pedagogical influences, which is confirmed by significant changes of the formation levels of safety skills of future teachers of physical culture in the experimental group in relation to the ones in control group.